2021
DOI: 10.3390/ijerph18041389
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Spatial Structure of the European Union’s Tourism Economy and Its Effects

Abstract: With the implementation of European integration policies such as the single market, the Euro and the Schengen Visa, the EU member states are developing closer economic ties through tourism, and their level of tourism integration is constantly improving. Taking the 28 EU member states as research objects, this paper constructs a tourism economic connection network among them, measures the strength of their tourism economic connections from 1995 to 2018 by using the modified gravity model and social network meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 63 publications
0
6
0
4
Order By: Relevance
“…*Correspondence: baizhongliang@ahmu.edu.cn; chenren2006@hotmail.com studies concluded that social network, which reflects the connection and interaction between different stakeholders, such as friendships, relatives, neighborhood, and social participation [10], could facilitate cross-sector collaboration [11][12][13]. Core members in social organizations include founders, leaders, legal representatives as well as managers who are familiar with the organizations.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…*Correspondence: baizhongliang@ahmu.edu.cn; chenren2006@hotmail.com studies concluded that social network, which reflects the connection and interaction between different stakeholders, such as friendships, relatives, neighborhood, and social participation [10], could facilitate cross-sector collaboration [11][12][13]. Core members in social organizations include founders, leaders, legal representatives as well as managers who are familiar with the organizations.…”
Section: Open Accessmentioning
confidence: 99%
“…Other studies have shown that cross-sector collaboration, which refers to the cooperation of government, social organization, and other institutions [ 8 ], could improve the quality and efficiency of social services, especially in health care services for the elderly [ 9 ]. The studies concluded that social network, which reflects the connection and interaction between different stakeholders, such as friendships, relatives, neighborhood, and social participation [ 10 ], could facilitate cross-sector collaboration [ 11 – 13 ]. Core members in social organizations include founders, leaders, legal representatives as well as managers who are familiar with the organizations.…”
Section: Introductionmentioning
confidence: 99%
“…The research pointed out that HSR can strengthen the aggregation effect, and the tourism nodes in the network can take advantage of the endowment of tourism resources, hospitality capacity, tourist transportation network density, etc. In addition, Xie et al (2021) constructed the spatial structure of the European Union (EU) by the modified gravity model and social network method. They analyzed the effects on the EU tourism economy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Berbagai penelitian mengenai ekonomi pariwisata telah banyak dilakukan, tetapi hanya sedikit yang membahas mengenai struktur kerjasama wilayah dalam ekonomi pariwisata. Penelitian yang membahas mengenai kerjasama ekonomi pariwisata yaitu dilakukan oleh Widyastuti, Marsoyo, and Setiawan (2019), Gan et al (2021), dan Xie, Li, and Yin (2021). Penelitian yang dilakukan oleh Widyastuti, Marsoyo, and Setiawan (2019) berpendapat bahwa jarak antar wilayah merupakan indikator utama wisatawan membentuk suatu rute wisata.…”
Section: Pendahuluanunclassified